The World Bank's "Employing Workers" index: Findings and critiques - A review of recent evidence. - LEE, Sangheon; McCANN, Deirdre; TORM, Nina (International Labour Review, 2008)
This note provides an update on the ongoing debate over the World Bank's Doing Business project with a particular focus on its "Employing Workers" index, which is intended to measure difficulty of hiring, rigidity of working hours and difficulty of firing. The authors review the findings of studies that have used this index or been influenced by it and of those that inspired its construction. They go on to examine criticisms of this instrument, highlighting both conceptual and empirical problems. Their paper concludes with suggestions for alternative approaches and future research.